Uji Efektivitas Salep Ekstrak Etanol Daun Mahkota Dewa (Phaleria Macrocarpa) Terhadap Luka Sayat pada Tikus Putih - Zulfikri Zulfikri; Zulfa Ismaniar Fauzi; Masrah Masrah; Khadizah Khadizah (JURNAL FARMASI DAN MAKANAN, 2024)
Mahkota Dewa is a medicinal plant that contains several active substances such as alkaloids, sapoins, tannins which can be used to affect collagen by inhibiting the production of wound tissue. The purpose of this study was to determine the effectiveness of the ethanol extract ointment from the leaves of Mahkota Dewa as a healer for cuts in white rats. This research is an experimental study, designed with a posttest Only Control Group design, where this study used the ethanol extract of Mahkota Dewa leaf ointment in three different concentrations: 5%, 10%, 15%, Povidone Iodine Ointment and Ointment Base. A number of 15 white rats were used as experimental animals. Mahkota Dewa Leaf Ethanol Extract Ointment with a concentration of 5%, 10%, 15% can heal cuts within 8 days, 7 days and 5 days respectively. Ointment with a concentration of 15% had almost the same healing time as the positive control, and the group given the ointment base (negative control) recovered on the 12th day. The conclusion of this study is that the ethanol extract of the leaves of Mahkota Dewa is effective in healing cuts in white rats.